The evolutionary patterns, expression profiles, and genetic diversity of expanded genes in barley - Tao, Wenjing; Li, Ruiying; Li, Tingting; Li, Zhimin; Li, Yihan; Cui, Licao (Frontiers in Plant Science, 2023)
Gene duplication resulting from whole-genome duplication (WGD), small-scale duplication (SSD), or unequal hybridization plays an important role in the expansion of gene families. Gene family expansion can also mediate species formation and adaptive evolution. Barley (Hordeum vulgare) is the world’s fourth largest cereal crop, and it contains valuable genetic resources due to its ability to tolerate various types of environmental stress. In this study, 27,438 orthogroups in the genomes of seven Poaceae were identified, and 214 of them were significantly expanded in barley. The evolutionary rates, gene properties, expression profiles, and nucleotide diversity between expanded and non-expanded genes were compared. Expanded genes evolved more rapidly and experienced weak negative selection. Expanded genes, including their exons and introns, were shorter; they had fewer exons; their GC content was lower; and their first exons were longer compared with non-expanded genes. Codon usage bias was also lower for expanded genes than for non-expanded genes; the expression levels of expanded genes were lower than those of non-expanded genes, and the expression of expanded genes showed higher tissue specificity than that of non-expanded genes. Several stress response-related genes/gene families were identified, and these genes could be used to breed barley plants with greater resistance to environmental stress. Overall, our analysis revealed evolutionary, structural, and functional differences between expanded and non-expanded genes in barley. Additional studies are needed to clarify the functions of the candidate genes identified in our study and evaluate their utility for breeding barley plants with greater stress resistance.